Evaluation of the Success of Enterprise Resource Planning in A Company Engaged in the Pharmaceutical Distribution with the Information System Success Model - Rayi Dwipanilih; Viany Utami Tjhin (LPPM STIKOM Tunas Bangsa, 2023)
The purpose of this study is to identify the elements that affect user satisfaction and the effectiveness of the implementation of the ERP system at PT Indofarma Global Medika as well as the elements that require improvement in order to boost the effectiveness of the ERP applications at PT Indofarma Global Medika. Information Quality, System Quality, and Service Quality are used as independent variables in this research. Use, user satisfaction, and net benefits are the dependent variables. The study's sample consists of actual users who are employed by PT Indofarma Global Medika in the departments of sales, purchasing, warehouse management, and financial accounting. The sample was taken using the purposive sampling technique. One hundred surveys were given directly to users who were actively collecting data using the questionnaire method. With statistical test hypothesis testing, the statistical approach employs multiple linear regression analysis. The validity test results demonstrate that the Cronbach's Alpha value is more than 0,7 indicating that the variable is legitimate for further testing. The p-values test findings reveal that system quality, information quality, service quality, and user happiness all significantly influence net benefits, whereas use has a less significant impact